The relationship between children’s emotional development tasks fulfilment and Strength and Difficulties Rutter Questionnaire assessment on elementary school-aged children’s mental health - Hidayati, Eni; Olina, Yanuan Ben; da Costa Freitas, Aureo Frutalegio; Martins, Adelina Frutalegio (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the emotional development of school-aged children.Method: The descriptive, analytical study was carried out on children of elementary schools in the Semarang City area in January 2022. Included were children aged 6-12 years with active elementary school status. Data was collected using the 25-item Strength and Difficulties Rutter Questionnaire. The questionnaire was filled manually by the subject along with theguardian or teacher. Data was analysed using SPSS 20.Results: Of the 326 children, 174(53.21%) were girls and 153(46.79%) were boys. Overall, 171(52.3%) subjects were aged <10 years, while 156(47.7%) were aged 10-12 years. There were 295(90.21%) children with normal prosocial behaviour, 206(63%) with normal emotional status, 264(80.73%) with normal conduct, 133(40.67%) with normal hyperactivity level, and 91(27.83%) with normal equation with peers.Conclusion: Different domains of the Strength and Difficulties Questionnaire showed varying degrees of pro-social behaviour, emotional status, conduct, hyperactivity level and peer interaction among the subjects.Keywords: Altruism, Mental, Emotional, Strength, questionnaire.